Cement space of all-ceramic crowns - Piras, Fernanda Furtado (2019)
A ceramic systems ability to provide a restoration well adapted and fulfilling the patients clinical and esthetic requirements is its most important technical feature. A CAD / CAM machine unit must be able of designing and milling different restorative materials, such as: resin-matrix ceramics, polycrystalline ceramics and glass-matrix ceramics. The purpose of this study was to present two articles that evaluated weather or not the milling strategy of different all-ceramic crown materials has an influence on the final cementation space. Specifically, the two articles evaluated: article I - The cementation space assessed by the most commonly used method- silicone replica technique- correlating stereomicroscope analysis with micromotomography (-CT); article II: The two-dimensional measures of cementation space were correlated with volume values by using -CT analysis, to better understand the behavior of 2D values in a tridimensional view. In both articles, single crowns were milled in lithium-disilicate, resin nanoceramic and zirconia. In article I, one hundred twenty measurements of each material were used to correlate the methodologies: stereomiscrocope and -CT. The Pearson correlation coefficient test showed a correlation between the methods (p= 0.000, r=+0.455). A similarity in the pattern of statistically significant differences among the regions evaluated (axial, occlusal, marginal) for both methodologies seems to exist. The positive correlation between the methods of measurements of cement space suggests that the internal dimensions of the materials varied because the different strategies after milled of them. In article II, twenty-eight slices were evaluated in three regions: marginal, axial and occlusal, totaling eighty-four measurements for each specimen. Axial and Marginal region showed positive correlation (p=0.000, r=+0.656; p=0.000, r=+0.677, respectively), while occlusal space presented negative correlation (p=0.003, r=0.526). The correlation between 2D and volumetric analysis allow to achieving as more information as possible to improve CAD/CAM systems.